Analisis Dampak Kondisi Jalan Buruk terhadap Kegiatan Ekonomi dan Sosial di Desa Padang Kuas Kec. Sukaraja, Kab. Seluma, Kota Bengkulu - Dinah Yusiana Salsabila; Jeni Efri Yani; Jenny Puspa Wulandari; Amelia; Nurhidayat Fajar Saputra; Ismail (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This research aims to analyze the impact of bad road conditions on economic and social activities in Padang Kuas Village, Sukaraja District, Seluma Regency, Bengkulu City. The poor road conditions in this village have become a serious problem that affects people's daily lives. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. The research results show that poor road conditions have a negative impact on economic activities, such as hampering the distribution of goods and services and increasing transportation costs. Apart from that, inadequate road conditions also hinder people's access to social facilities such as schools, health centers and places of worship, which ultimately affects their quality of life. This study suggests the need for attention from the local government to immediately improve road infrastructure in order to improve the economic and social welfare of the people of Padang Kuas Village.